2002
DOI: 10.1074/jbc.m108328200
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Postnatal Survival and Altered Body Weight Regulation in Procolipase-deficient Mice

Abstract: In vitro, pancreatic triglyceride lipase requires colipase to restore activity in the presence of inhibitors, like bile acids. Presumably, colipase performs the same function in vivo, but little data supports that notion. Other studies suggest that colipase or its proform, procolipase, may have additional functions in appetite regulation or in fat digestion during the newborn period when pancreatic triglyceride lipase is not expressed. To identify the physiological role of procolipase, we created a mouse model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 28 publications
0
45
1
Order By: Relevance
“…The importance of colipase in the digestion of fat was indicated in a clinical report of steatorrhea in two brothers with a congenital absence of colipase, which indicated that the steatorrhea decreased with the administration of colipase (76). It has also been demonstrated in colipase-deficient mice (41), which, when placed on a high-fat diet, developed steatorrhea that was so severe that undigested lipids could be seen in their feces. When these mice were placed on a low-fat diet, their ability to digest fat returned to normal.…”
Section: Digestion and Absorption Of Lipids: A Brief Overviewmentioning
confidence: 87%
“…The importance of colipase in the digestion of fat was indicated in a clinical report of steatorrhea in two brothers with a congenital absence of colipase, which indicated that the steatorrhea decreased with the administration of colipase (76). It has also been demonstrated in colipase-deficient mice (41), which, when placed on a high-fat diet, developed steatorrhea that was so severe that undigested lipids could be seen in their feces. When these mice were placed on a low-fat diet, their ability to digest fat returned to normal.…”
Section: Digestion and Absorption Of Lipids: A Brief Overviewmentioning
confidence: 87%
“…In addition, when knock-out mice were fed a high-fat diet, they exhibited fat malabsorption through steatorrhoea (71) . Crystallographic analysis suggests that colipase binds to the non-catalytic, C-terminal domain of pancreatic lipase (5) .…”
Section: Colipasementioning
confidence: 99%
“…Within this conversion, a five-amino acid fragment is lost. This pentapeptide, also referred to as enterostatin (70) , has been suggested to be important in appetite control in animal studies (71) . Due to shared pathways of secretion, a similar range of neurohumoral mediators is likely to affect up-and downregulation of procolipase release as that of pancreatic lipase (see above).…”
Section: Colipasementioning
confidence: 99%
“…have steatorrhea and decreased body weight (5). Colipase is secreted as a proform, procolipase, which is processed in the intestine to release colipase and a pentapeptide named enterostatin.…”
mentioning
confidence: 99%